Edukasi dan Pelatihan Kultur Plankton sebagai Pakan Alami Budidaya Ikan di Desa Wonoasri, Kecamatan Grogol, Kabupaten Kediri - Inayah, Zakiyyah Nur; Pratama, Adif; Fajr, Muhammad Bilal Afrizal; Fadila, Wahyu Nur; Aulia, Muhamad Fajar (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
Freshwater fish farming plays a crucial role in food self-sufficiency, particularly in rural areas. However, high feed costs and uncertain availability often pose significant obstacles to this activity. This problem is also felt in fish farming activities in Wonoasri Village, Grogol District, Kediri Regency, where cultivation practices rely on manufactured feed. This directly affects the sustainability and productivity of fish. Limited knowledge about alternative natural feeds results in suboptimal cultivation productivity. Therefore, this community service aims to provide solutions to these problems through education and training in plankton culture for Women Farmers Groups (KWT). This community service activity was carried out on August 13, 2025, with five participants. The activity implementation method includes three stages: preparation, implementation, and evaluation. Preparation for the activity included surveys, observations, coordination, and preparation of tools, materials, and resources. The activity implementation included the presentation of theoretical material on plankton (definition, types, and roles in fish farming) and a demonstration of plankton culture and its application in fish farming. The culture training used used gallons with seeds from pure cultures of Chlorella pyrenoidosa and local cultivation water. Evaluation is carried out by administering pretests and posttests, as indicators of the success of the activity. The evaluation results showed an increase in participants' knowledge, understanding, and skills regarding plankton in fish farming, as demonstrated by the pretest and posttest results given to participants. The activity took place interactively, with questions and answers from participants during the presentation and demonstrations. Participants were enthusiastic and committed to independently cultivating plankton as natural feed for fish farming, thereby increasing productivity. This activity is expected to improve feed cost efficiency, encourage fish farming productivity, and support food security programs and sustainable village economic progress.